THE IMPACT OF CURRICULUM CHANGES ON THE QUALITY OF ELEMENTARY SCHOOL LEARNING IN INDONESIA - Dwi Mahya Sari; Fathur Rahman; Ibnu Ripant; Novalisa Puspitasari; Rangga Firdaus (Jurnal Ilmu Pendidikan Indonesia, 2026)
Curriculum changes are not just a change of documents, but must reflect the country's struggle in facing social, technological, and globalization developments. The study used a systematic literature review method by examining more than fifty reputable journal articles (Scopus index) in the last five years as well as several relevant local primary sources. The analysis found that the independent curriculum provides flexible space for schools and teachers to develop project-based learning and Pancasila student profiles. However, challenges are still found such as teacher unpreparedness, digital infrastructure disparities, science literacy gaps, and differences in implementation between regions. This article provides recommendations on teacher capacity building, structuring curriculum change management, strengthening collaboration between schools and communities, and improving digital literacy and instilling local cultural values. These findings are expected to help policymakers, researchers, and practitioners design curriculum policies that are more responsive to the needs of the 21st century while maintaining national identity.